1972
DOI: 10.1136/bmj.3.5829.756
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Electrical Stimulus for Prevention of Deep Vein Thrombosis

Abstract: The most effective electrical stimulus to the calf muscles which prevents stasis in the soleal veins during operation was determined. This was subsequently used in a clinical trial and was shown to produce a 92% relative reduction in the incidence of deep vein thrombosis as determined by the (125)I-fibrinogen test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 14 publications
(1 reference statement)
0
44
0
4
Order By: Relevance
“…Izumi et al 23 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Nicolaides et al 33 Browse and 29 found a significant reduction in the incidence of DVT in low-dose heparin plus electrical stimulation group [7% (95% CI ¼ 0.4 À 33.9)] compared to either low-dose heparin (50%) or placebo groups [47% (95% CI ¼ 23.9 À 71.5%)]. In this study, 125-I fibrinogen scan and impedance plethysmography followed by confirmatory venography were used for diagnosing DVT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Izumi et al 23 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Nicolaides et al 33 Browse and 29 found a significant reduction in the incidence of DVT in low-dose heparin plus electrical stimulation group [7% (95% CI ¼ 0.4 À 33.9)] compared to either low-dose heparin (50%) or placebo groups [47% (95% CI ¼ 23.9 À 71.5%)]. In this study, 125-I fibrinogen scan and impedance plethysmography followed by confirmatory venography were used for diagnosing DVT.…”
Section: Discussionmentioning
confidence: 98%
“…On the NOAS for observational studies, both Nicolaides et al 33 and Browse and Negus 34 were awarded 4 points for selection, 1 point for comparability and 3 points for outcome.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Perioperative NMES has been previously investigated on patients during general elective surgery while under anesthesia, with mostly positive results [1,3,4]. While there has been a demonstrated reduction in DVT rates in general surgery associated with the use of neuromuscular electrical stimulation (NMES); the clinical use of calf muscle NMES as DVT prevention methodology has yet to be established [3,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite early reports indicating the effectiveness of NMES at preventing DVT in general surgical patients, the technique has not gained the same widespread acceptance as other mechanical techniques such as intermittent pneumatic compression or graduated compression stockings [1][2][3][4]. Early implementations of NMES devices were so uncomfortable that they could only be used when the patient was under anaesthetic [1].…”
Section: Introductionmentioning
confidence: 95%
“…Важно, что профилактическая эффективность ЭМС может распространяться и на нестимулированную конеч-ность [23,24]. Кроме того, ЭМС, по-видимому, оказывает системные эффекты.…”
Section: механическая перемежающая компрессия нижних конечностейunclassified